Disaggregating innovation for sustainable development in ASEAN: Panel evidence on the moderating role of government effectiveness - Pureheart Ogheneogaga Irikefe; Mohammad Falahat; Ahmad Danial Zainudin; Ihtisham Ullah; Nohman Khan; Bernard Ojonugwa Anthony (PLoS ONE, 2026)
With progress toward the 2030 Agenda faltering, many see innovation as a key to sustainable development. The Association of Southeast Asian Nations (ASEAN) bloc represents a unique opportunity to examine how innovation capabilities drive sustainability in diverse economic and developmental contexts. Using panel data for ASEAN countries from 2011 to 2022, this study breaks down innovation into the seven pillars of the Global Innovation Index (GII) and investigates their impact on the Sustainable Development Goal (SDG) Index; with the objective of identifying which GII pillars most strongly predict SDG, while examining the moderating role of government effectiveness and controlling the impacts of gross national income per capita and foreign direct investment. Fixed effects models were used to analyse the data and supplemented by Driscoll-Kraay standard errors, addressing unobserved heterogeneity and cross-sectional dependence. Results reveal that only Institutions and Infrastructure pillars exert a consistently positive impact on SDG performance. In contrast, Creative Outputs have a negative impact. Importantly, Government Effectiveness reverses the negative impact of Creative Outputs, so that this pillar becomes positive for SDG achievement, without significant moderation of the other six GII pillars when controlling for year effects. In conclusion, these findings contest the efficacy of universal innovation policies and underscore the imperative for nuanced, context‑specific ones. It is recommended that ASEAN governments prioritize institutional and infrastructural investments and develop tailored regulatory frameworks, such as green intellectual property regimes and digital economy standards, to harness the creative economy for inclusive, sustainable growth by explicitly integrating innovation strategies with governance reforms.